ปัจจัยที่มีผลต่อการเปลี่ยนแปลงชายฝั่งตั้งแต่แหลมผักเบี้ยจังหวัดเพชรบุรีถึงเขาตะเกียบจังหวัดประจวบคีรีขันธ์ - สร้อยวิสา สร้อยคำ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The changing coastlines from Lam Phak Bia Changwat Petchabri to Kao Ta Kiab Changwat Prachuap Kirikhan were studied using Lansat TM-5 data from year 1987, 1988, 1994, 1998, 1999 and 2002 and SPOT data from year 1988, 1989, 1993, 1994 and 1995. Image Registration technique were carried out to analyze the data from those different dates. Analysis results showed both accretion and deposition at different areas along the shoreline. Though, the changing rates were small. When studying the physical factors such as wind, wave, current and near-shore sediment transport that might influence shoreline changes, it was found that monsoonal wind-generated wave and wind-driven circulation controlled near-shore sediment transport. During northeast monsoon season, wave and long-shore current generated by northerly and northeasterly winds caused southward long-shore sediment transport while the weather and coastal conditions during the southwest monsoon season caused northward long-shore sediment transport. Even though the wind and wave conditions were stronger during the northeast monsoon season, the net annual sediment transport was northward because the southwest monsoon lasted longer than the northeast monsoon. Man-made coastal structures also affected shoreline changes in the study area. Shore-normal structures such as breakwater or jetties obstructed natural long-shore sediment transport. The sediment was deposited on the front side, causing shoreline progression while the sediment on the lee-wave side was eroded, causing shoreline recession. Vegetation also played the role in shoreline change. Mangrove area tended to sustain the muddy sediment, causing the progressing of the shoreline.